Soil Application of Zinc for Potato Biofortification in the Central Andes of Peru - Fernando Chung-Montoya; Victorio Melendres-Herrera; Vanessa Pilatarzi-Vilchez; Angely Sinche-Ambrosio; Jesús Vera-Vilchez; Ruby Vega-Ravello; Sady García-Bendezú (Journal of Soil Science and Plant Nutrition, 2026)
Zinc is essential for human health, yet dietary deficiencies persist in many regions. This study evaluated the effectiveness of soil-applied zinc to enhance zinc content in potato tubers grown in Peru’s central Andes, as an agronomic biofortification strategy. Field trials were conducted over two seasons in four Andean sites using five Zn rates (0–32 kg ha⁻¹). One variety was tested in 2016–2017, and four in 2017–2018. Yield, Zn content, accumulation, partial balance, and dietary contribution were assessed. In both seasons, Zn fertilization did not significantly affect tuber yield. In 2016–2017, Zn content in tubers increased by up to 86% and accumulation by 74% at 16 kg Zn ha⁻¹. The estimated dietary contribution rose by 79%, with Achoscuyo showing the highest response and Lucma the lowest. Site differences were more evident at intermediate and high doses. In 2017–2018, Zn accumulation in shoots exceeded that in tubers by up to 2.8-fold, and Zn content in the peel was twice that of the flesh. Maximum Zn content and accumulation varied among varieties and doses. Canchán and Perricholi showed high Zn content and accumulation at 16 kg Zn ha⁻¹. Principal component analysis revealed that Zn dose was positively associated with Zn content and negatively with tuber yield. The response to Zn fertilization depended on site, dose, and genotype. Soil-applied Zn increased Zn content in potatoes without compromising yield. Selecting varieties with high tuber Zn accumulation improved nutritional outcomes and fertilizer use efficiency.